Regional Response to Crisis Situations: Identification of Hysteresis Processes - Irina Danilova; Irina Savelieva; Natalya Pravdina; Aleksandr Rezepin (Communications of International Proceedings, 2020)
The shocks in the economies of developing countries in recent years associated with the impact of the global crisis of 2008-2009, internal macro-economic situations, and in the Russian Federation of sanctions and anti-sanctions in 2013-2014, cause increased attention to the stability and shock resistance of the economies of countries and regions. The article presents one of the methods for assessing the known fact of memory about shocks, violations, crises, which is considered as a property of unique adaptability to force majeure situations that stimulate the aggregation of reserves of stability and resistance of the economy to destructive factors. On the example of the monospecialized regions of the Russian Federation of the same type in the main industry, depending on the world market conditions, an assessment of the presence of the hysteresis phenomenon was carried out. The differences between the two crisis periods of 2007-2008 and 2013-2014 are detailed from the standpoint of the duration and speed of phase processes (decline, recovery, and growth), the depth of the fall, the variability of parameters in terms of the "index of industrial production". The identification and assessment of hysteresis allows us to expand our understanding of the adaptability of the economy of the Russian Federation and supporting regions, to focus on the uniqueness of development paths, comparative advantages of economic efficiency and the specifics of structural reactions. The article provides an overview of approaches to the analysis and assessment of region resilience and the peculiarities of its implementation in developing countries, to which the Russian Federation be-longs. The author's approach to the assessment is presented on the example of four regions of Russia. The study was carried out on the example of regions with similar sectoral structure as the most significant factor influencing impact resistance to crises and shocks.
Keywords: Resilience; Impact Resistance; Economic Hysteresis; Regional Economic Development; Regional Reactions to Shock.